Some weighted integral inequalities for differentiable beta-convex functions. Issue 2 (17th February 2022) - Azzouza, N.; Meftah, B.
Abstract: In this paper, we establish some new weighted Hermite-Hadamard type inequalities for functions whose modulus of the first derivatives are beta-convex. Several known results are also obtained. Applications to random variables and special means are given.